Gene Transfer of Glutamic Acid Decarboxylase 67 by Herpes Simplex Virus Vectors Suppresses Neuropathic Pain Induced by Human Immunodeficiency Virus gp120 Combined with ddC in Rats. (June 2015) - Kanao, Megumi; Kanda, Hirotsugu; Huang, Wan; Liu, Shue; Yi, Hyun; Candiotti, Keith A.; Lubarsky, David A.; Levitt, Roy C.; Hao, Shuanglin
<x xml:space="preserve">Abstract</x> BACKGROUND: Human immunodeficiency virus (HIV)-related painful sensory neuropathies primarily consist of the HIV infection–related distal sensory polyneuropathy and antiretroviral toxic neuropathies. Pharmacotherapy provides only partial relief of pain in patients with HIV/acquired immune deficiency syndrome because little is known about the exact neuropathological mechanisms for HIV-associated neuropathic pain (NP). Hypofunction of γ-aminobutyric acid (GABA) GABAergic inhibitory mechanisms has been reported after peripheral nerve injury. In this study, we tested the hypothesis that HIV gp120 combined with antiretroviral therapy reduces spinal GABAergic inhibitory tone and that restoration of GABAergic inhibitory tone will reduce HIV-related NP in a rat model. METHODS: The application of recombinant HIV-1 envelope protein gp120 into the sciatic nerve plus systemic ddC (one antiretroviral drug) induced mechanical allodynia. The hind paws of rats were inoculated with replication-defective herpes simplex virus (HSV) vectors genetically encoding gad1 gene to express glutamic acid decarboxylase 67 (GAD67), an enzyme that catalyzes the decarboxylation of glutamate to GABA. Mechanical threshold was tested using von Frey filaments before and after treatments with the vectors. The expression of GAD67 in both the lumbar spinal cord and the L4-5 dorsal root ganglia was examined using western blots. The expression of mitochondrial superoxide in the spinal dorsal horn was examined using MitoSox imaging. The immunoreactivity of spinal GABA, pCREB, and pC/EBPβ was tested using immunohistochemistry. RESULTS: In the gp120 with ddC-induced neuropathic pain model, GAD67 expression mediated by the HSV vector caused an elevation of mechanical threshold that was apparent on day 3 after vector inoculation. The antiallodynic effect of the single HSV vector inoculation expressing GAD67 lasted >28 days. The area under the time–effect curves in the HSV vector expressing GAD67 was increased compared with that in the control vectors (P = 0.0005). Intrathecal GABA-A/B agonists elevated mechanical threshold in the pain model. The HSV vectors expressing GAD67 reversed the lowered GABA immunoreactivity in the spinal dorsal horn in the neuropathic rats. HSV vectors expressing GAD67 in the neuropathic rats reversed the increased signals of mitochondrial superoxide in the spinal dorsal horn. The vectors expressing GAD67 reversed the upregulated immunoreactivity expression of pCREB and pC/EBPβ in the spinal dorsal horn in rats exhibiting NP. CONCLUSIONS: Based on our results, we suggest that GAD67 mediated by HSV vectors acting through the suppression of mitochondrial reactive oxygen species and transcriptional factors in the spinal cord decreases pain in the HIV-related neuropathic pain model, providing preclinical evidence for gene therapy applications in patients with HIV-related pain states.